IbM DUSUN KRAJAN PELATIHAN PENGELOLAAN KUE BROWNIES DAN KUE NUGGHETS BERBAHAN TANAMAN UMBI – UMBI AN (JALAR) - Ida Bagus Cempena; Ida Ayu Nuh Kartini; Ninik Martini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
Pacitan precisely in Krajan Wonodadi Kulon Ngadirojo, geographically wide area 891.88 ha, the majority of the land in the form tegal / fields covering an area of 420.53 ha. Potential in Agricultural Sector became the leading commodity contribute greatly to the economic development, both directly the raw material used and processed through a management process of making a cake. Commodity raw materials from the agricultural sector are: Clove, Coconut, Cassava, Banana, Bluebird, Melinjo, and Tuber (Sweet), who plays prop improve household incomes and expanding employment opportunities are raw materials tubers (Potato) processed form : Cakes (Brownies, Nugghets). Given the great desire of the group Partners Household Small Business to supplement the family income, then Program (IbM) wants to realize by means of procurement (TTG) in the form of machines and provide a wide range of training business groups cakes made from local plants Bulbs - tubers (Potato). Procurement of Appropriate Technology (TTG) in the form of machine is very helpful for a smooth production process from traditional to technology moderan, while by getting the various training areas of management will broaden pengetahuanya Partners Small Business, towards the preparation of implementing entrepreneurship in the management of baking brownies and cakes Nugghets based tubers (Potato). The results are very encouraging in the presence of procurement (TTG) in the form of machine Ovens and Machines Mixer, the production process is increasing and growing rapidly, while also implementing various management training to make the performance of Partners Small Businesses increasingly innovative in developing a business to make a cake made from plant ts ( Potatoes)Keywords : Management of Appropriate Technology (TTG) Cakes Brownies and Cake Nugghets Made from plantÂ Tubers (Potato)